Anti-Nuclear Antibodies Patterns in Patients With Systemic Lupus Erythematosus and Their Correlation With Other Diagnostic Immunological Parameters - Al-Mughales, Jamil A. (Frontiers in Immunology, 2022)
Background Antinuclear antibodies (ANA) are major immunodiagnostic tools in systemic lupus erythematosus (SLE); however, their clinical and pathogenic roles are not yet elucidated and are a subject of controversy. Objectives The aim of the study is to explore the pathogenic significance of ANA patterns among SLE patients, by analyzing their association with ANA titers, complement levels and other pathogenic immune markers, namely, anti-double-stranded DNA (anti-dsDNA), complements C3 and C4, rheumatoid factor (RF), anticardiolipin antibodies IgG (ACL IgG) and IgM (ACL IgM), Beta-2 Glycoprotein 1 Antibodies (β2-GP) IgG (β2-IgM) and IgM (β2-IgM), and lupus anticoagulant (LA). Method A comparative cross-sectional study was conducted among 495 SLE patients, who were diagnosed and classified by consultant rheumatologists according to the new European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) 2019 criteria. SLE immunodiagnostic profiles were analyzed including the following parameters: ANA antibody titers and staining patterns, anti-dsDNA, C3 and C4 levels, aCL, and anti-β2-GP and LA. Result The most frequently observed ANA patterns were the speckled (52.1%) and homogeneous (35.2%) patterns, while other patterns were rare representing less than 7% of the patients each. ANA titers were highest in patients with mixed pattern followed by the speckled pattern. Of all the investigated patterns, the peripheral pattern showed the most pathogenic immune profile, namely, highest levels of anti-dsDNA, lowest levels of C4, and highest levels of aCL and β2-GP IgG and IgM. Conclusion This retrospective study showed that speckled followed by homogeneous ANA patterns were predominant accounting for 52.1 and 35.2% of the patients. The ANA pattern showed several associations with other immune markers that are documented to have significant clinical implications in SLE. Peripheral, mixed, and speckled patterns were associated with higher profiles of immune markers indicative of a potential prognostic value of these patterns in SLE.